2016
DOI: 10.1177/1474704916643459
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Jessica Rabbit Sexy? Contrasting Roles of Waist and Hip Size

Abstract: While waist/hip ratio (WHR) and body mass index (BMI) have been the most studied putative determinants of female bodily attractiveness, BMI is not directly observable, and few studies have considered the independent roles of waist and hip size. The range of attractiveness in many studies is also quite limited, with none of the stimuli rated as highly attractive. To explore the relationships of these anthropometric parameters with attractiveness across a much broader spectrum of attractiveness, we employ three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 75 publications
6
62
1
Order By: Relevance
“…In other words, the WHR = .68 obtained in the present study (global context) is far from extremely supernormal WHRs of caricatures, cartoon characters and other artistic stylizations (cf. Lassek & Gaulin, 2016), but it is closer to WHRs measured in 'normally supernormal' females such as Playboy centerfolds (cf. Voracek & Fisher, 2002).…”
Section: Preference For Average -Supernormalsupporting
confidence: 56%
“…In other words, the WHR = .68 obtained in the present study (global context) is far from extremely supernormal WHRs of caricatures, cartoon characters and other artistic stylizations (cf. Lassek & Gaulin, 2016), but it is closer to WHRs measured in 'normally supernormal' females such as Playboy centerfolds (cf. Voracek & Fisher, 2002).…”
Section: Preference For Average -Supernormalsupporting
confidence: 56%
“…However, a low waist-to-hip ratio and low BMI is strongly associated with youth and nubility (Andrews, Lukazweski, Simmons, & Bleske-Recheck, 2017;Fisher 1992;Lassek & Gaulin, 2016, 2018a, 2018b-that is, a woman having reached puberty and accumulated the type of body fat (omega 3 fatty acids) that is critical to a child's brain development (and which tends to be deposited on a woman's hips and thighs). This may seem like a fine distinction, but as…”
Section: Existing Research On Long-term Familial Bondsmentioning
confidence: 99%
“…Thus, we hypothesized that lower WHR, WSR, and WBR would be positively correlated with higher rankings. Recent studies also reported that WSR influences our perception of attractiveness in females more than WHR (Andrew et al, 2017;Lassek & Gaulin, 2016). Thus, we hypothesized that WSR, in comparison to WHR, is a more important factor on the rankings of plus-size models.…”
Section: Current Studymentioning
confidence: 80%
“…Over the years, several anthropometric measures have been proposed by evolutionary psychologists as cues of health and fertility in females. These anthropometric measures include, but are not limited to, waist-to-hip ratio (WHR), body mass index (BMI), waist-to-bust ratio (WBR), and waist-to-stature ratio (WSR) (Fisher & Voracek, 2005;Kościński, 2014;Lassek & Gaulin, 2016;. Although evolutionary psychology studies are oftentimes concerned with functional explanations (e.g., Andrews, Lukaszewski, Simmons, & Bleske-Rechek, 2017; Jasien śka, Ziomkiewicz, Ellison, Lipson, & Thune, 2004;Singh, 1993), a more multifaceted understanding of why certain anthropometric measures determine female attractiveness in humans can be benefited by Tinbergen's four questions (Tinbergen, 1963).…”
Section: Anthropometric Measures As Cues Of Health and Fertility In Fmentioning
confidence: 99%
See 1 more Smart Citation